Red traitor : a novel - Matthews, Owen (Doubleday, 2021)
"The year is 1962, and KGB Lieutenant Colonel Alexander Vasin is chasing a white elephant: the long-rumored existence of an American spy embedded at the highest echelon of Soviet power. In a wild-goose chase that has Vasin engaged in high-stakes espionage against a rival State agency, he first hears whispers of an ominous top-secret undertaking: Operation Anadyr. As tensions flare between Nikita Khrushchev and President Kennedy over Russian missiles hidden in Cuba, four Soviet submarines are ordered to make a covert run at the American blockade in the Caribbean--each sub carrying tactical ballistic missiles armed with thermonuclear warheads. Critically acclaimed novelist Owen Matthews has crafted an incredibly taut thriller around one of the most treacherous moments in modern history, where the fate of the world rested on the itchy trigger finger of one lone Soviet naval officer, 100-meters under the sea, out of all contact with his commanders."--